Ceramic Pigments with the Diortosilicate Structure Based on the Dicalcium Silicate; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Sedelnikova M. B. Mariya Borisovna; Pautova Yu. I. Yuliya Igorevna; Pogrebenkov V. M. Valeriy Matveevich; Shulzhenko A. S. (Advanced Materials and Nanotechnology, 2014)
Title screen